2010
DOI: 10.1007/s11947-010-0365-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ultraviolet Light on Microbial Inactivation and Quality Attributes of Apple Juice

Abstract: Non-thermal technologies such as UV irradiation can offer advantages for minimal processing of transparent beverages. In this study, reconstituted apple juice was exposed to UV light in a continuous laboratory scale system at energy dosages ranging from 2.66 to 53.10 J/cm 2 by changing the exposure time. Treated juices were then evaluated for microbial inactivation and selected physical and chemical attributes. Product quality was further assessed by sensory evaluation using a 30-member consumer panel. Microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
102
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 30 publications
(31 reference statements)
14
102
0
2
Order By: Relevance
“…There were no significant differences between untreated (control), UV-C-treated and heat-treated LMJ blends in terms of pH (3.92-3.93) and titratable acidity (0.48-0.51%) (p b 0.05). Our results were in agreement with other studies reporting no significant changes in pH and titratable acidity of different types of fruit juices treated with UV-C light and heat treatment (Caminiti et al, 2012;Falguera, Pagan, & Ibarz, 2011;Noci et al, 2008;Pala & Toklucu, 2011.…”
Section: Effect Of Uv-c and Heat Treatment On The Physicochemical Prosupporting
confidence: 93%
“…There were no significant differences between untreated (control), UV-C-treated and heat-treated LMJ blends in terms of pH (3.92-3.93) and titratable acidity (0.48-0.51%) (p b 0.05). Our results were in agreement with other studies reporting no significant changes in pH and titratable acidity of different types of fruit juices treated with UV-C light and heat treatment (Caminiti et al, 2012;Falguera, Pagan, & Ibarz, 2011;Noci et al, 2008;Pala & Toklucu, 2011.…”
Section: Effect Of Uv-c and Heat Treatment On The Physicochemical Prosupporting
confidence: 93%
“…In raspberry nectar (light reddish), it was observed a decrease in the antioxidant capacity during the UV-C light processing; a decrease from 65 to 15 mg T/100 mL of nectar was observed. Similar results were found by Caminiti, Palgan, Muñoz, Noci, Whyte, & Morgan (2012) who indicated that in clear juices, such as clarified apple juice and raspberry juice, as the exposition time increased, the antioxidant capacity decreased because of a greater penetration of the UV-C light. Another important factor that can contribute to a decrease in the antioxidant capacity of raspberry nectar is the ascorbic acid content.…”
Section: Antioxidant Compoundssupporting
confidence: 84%
“…The explanation to the reduction of pigments in fruit products is because UV-C light may affect the structures of some compounds. Pala & Toklucu (2011) reported no significant differences (p > 0.05) in the content of phenolic compounds in pomegranate juices after UV-C light treatment; the same findings were reported by Caminiti, Palgan, Muñoz, Noci, Whyte, & Morgan (2012) in apple juice. The nectar that was more effected on TPC by the UV-C light was the blueberry nectar; this fact can be attributed to the inactivation of phenolic such as hydroxycinnamic acids and, or flavonols (Manach, Scalbert, Morand, Remesy, & Jimé nez, 2004) found in this fruit.…”
Section: Total Phenolic Compoundssupporting
confidence: 62%
“…The average values of the total soluble solids and pH, after UV-C light treatment, were 6.79±0.04 and 5.93±0.07 %, respectively. A number of researchers have reported that UV-C light did not have effect on pH, total soluble solids, and titratable acidityof fruit juices (Noci, Riener, Walkling, Cronin, Morgan & Lying, 2008;Caminiti et al, 2010;Pala & Toklucu, 2011). Table 2 presents the L, a, b, and ΔE color parameters of pitaya juice treated with UV-C light for 25 minutes.…”
Section: Physicochemical Characteristicsmentioning
confidence: 99%
“…Despite of this and due to the presence of colored compounds, organic compounds, and suspended matter, characteristic that may affect the UV-C light penetration into the liquid food product, the light transmission might be attenuated. As a result theUV-C light efficiency could be reduced (Caminiti et al, 2010).…”
mentioning
confidence: 99%